Maria in Hymnus und Sequenz. Interdisziplinäre mediävistische Perspektiven - Wegener, Lydia (Liturgie und Volkssprache. Studien zur Rezeption und Produktion geistlicher Lieder in Mittelalter und Früher Neuzeit, 2017)
Marian hymns and sequences occupy a central place in the history of sacred song. Alongside Latin poetry, starting from the early Middle Ages, there were also vernacular translations, which adapted, modified, and transformed the image of Mary from their original models. The conference volume assembles a broad range of interdisciplinary papers that examine these processes of reformulation and appropriation.